Spot urine sodium in acute heart failure: differences in prognostic value on admission and discharge. (1st May 2021) - Biegus, Jan; Zymliński, Robert; Fudim, Marat; Testani, Jeffrey; Sokolski, Mateusz; Marciniak, Dominik; Ponikowska, Barbara; Guzik, Mateusz; Garus, Mateusz; Urban, Szymon; Ponikowski, Piotr
Abstract: Aims: Most studies examined spot urine sodium's (sUNa + ) prognostic utility during the early phase of acute heart failure (AHF) hospitalization. In AHF, sodium excretion is related to clinical status; therefore, we investigated the differences in the prognostic information of spot UNa + throughout the course of hospitalization for AHF (admission vs. discharge). Methods and results: The study population were AHF patients ( n  = 172), who survived the index hospitalization. We compared the relationship between early (on admission, at 24 and 48 h) and discharge sUNa + measurements with post‐discharge study endpoints: composite of 1 year all‐cause mortality and AHF rehospitalization (with time to first event analysis) as well as with each event in separation. There were 49 (28.5%) deaths, 40 (23.3%) AHF rehospitalizations, while the composite endpoint occurred in 69 (40.1%) during 1 year follow‐up. The sUNa + had prognostic significance for the composite endpoint when assessed on admission, at 24 and at 48 h: hazard ratios (HRs) with 95% confidence intervals (CIs) (per 10 mmol/L) were 0.88 (0.82–0.94); 0.87 (0.81–0.91); 0.90 (0.84–0.96), all P  < 0.005. In contrast to early, active decongestion phase, discharge sUNa + had no prognostic significance HR (95% CI) (per 10 mmol/L): 0.99 (0.93–1.06) P  = 0.79 for the composite endpoint, which was independent from the dose of oral furosemide prescribed at that timepoint (average causal mediation effects: −0.38; P  = 0.71). Similarly, discharge sUNa + was neither associated with 1 year mortality HR (95% CI) (per 10 mmol/L): 0.97 (0.89–1.05) P  = 0.48 nor with AHF rehospitalizations HR (95% CI) (per 10 mmol/l): 1.03 (0.94–1.12), P  = 0.56. The comparison of longitudinal profiles of sUNa + during hospitalization showed significantly higher values within the early, active decongestive phase in those who did not experience composite endpoint when compared with those who did: admission: 94 ± 34 vs. 76 ± 35; Day 1: 85 ± 36 vs. 65 ± 37; Day 2: 84 ± 37 vs. 67 ± 35, all P  < 0.005 (mmol/L), respectively. There was no difference between those groups in discharge sUNa + : 73 ± 35 vs. 70 ± 35 P  = 0.82 (mmol/L). Conclusions: Spot UNa + assessed at early phase of hospitalization and at discharge have different prognostic significance, which confirms that it should be always interpreted along with clinical context.